Gender differences in the association between the triglyceride-glucose index and peripheral artery disease in vascular surgery inpatients aged 50 and above: a retrospective cross-sectional study - Li, Zhi-wei; Zhou, Peng; Shi, Bei-hao; Gong, Ya-qin; Lu, Ke; Zhu, Jian (Frontiers in Endocrinology, 2025)
BackgroundPeripheral artery disease (PAD) is a critical manifestation of systemic atherosclerosis, significantly affecting vascular health. Insulin resistance (IR) plays a central role in PAD pathophysiology. The triglyceride-glucose index (TyGI), a recognized marker of IR, has limited evidence regarding its association with PAD. This study aimed to investigate the relationship between the TyGI and PAD among vascular surgery inpatients aged over 50 in Kunshan, China, offering insights into clinical prevention and risk assessment of PAD.MethodsA retrospective cross-sectional study was conducted on 5923 patients (aged ≥ 50 years) admitted to the vascular surgery department of the Affiliated Kunshan Hospital of Jiangsu University, Suzhou, China, from December 2017 to August 2024. The TyGI was the exposure variable, while PAD, defined as PAD-like symptoms with an ankle-brachial index (ABI) < 0.9, was the outcome variable. Covariates included age, sex, body mass index (BMI), smoking status, alcohol consumption, hypertension, diabetes, low-density lipoprotein (LDL), total cholesterol (TC), alanine aminotransferase (ALT), and neutrophil counts (NEUT). Multiple logistic regression, subgroup analysis, curve fitting, and threshold effect analysis were performed.ResultsAfter adjusting for covariates, the TyGI showed a significant positive association with PAD (OR = 1.92, 95% CI: 1.50–2.45, P < 0.001). When classified by TyGI quartiles, individuals in the highest quartile had a significantly increased risk of PAD (OR = 2.19, 95% CI: 1.43–3.35, P < 0.001). Subgroup analysis revealed a significant interaction effect of gender on the TyGI-PAD relationship (P for interaction < 0.05). In male patients, the TyGI showed a positive linear correlation with PAD, whereas in female patients, a positive nonlinear relationship was observed, with a threshold value of 9.68.ConclusionThis study demonstrates a significant positive association between TyGI and PAD in vascular surgery inpatients aged 50 and older, with a gender-specific difference in the nature of this relationship. A linear correlation was found in male patients, while in female patients, the association was nonlinear, with a threshold effect. These findings provide relevant evidence for understanding the role of the TyGI in peripheral vascular health and could aid in the clinical assessment and management of PAD.